Multiple co-occurring genetic variants in an elderly patient with Liddle’s-like syndrome: a case report and literature review - Yunlong Liang; YangZhi Zheng; Hua Yuan; Li Guo; Xinping Wang; Jing Zhang; Juan Wang; Yanhai Zhang; Linan Duan (Journal of Medical Case Reports, 2026)
Abstract Background Liddle syndrome (LS) is a rare autosomal dominant condition classically defined by early-onset hypertension, hypokalemia, metabolic alkalosis, and a suppressed renin-aldosterone profile, primarily driven by gain-of-function mutations in the SCNN1A , SCNN1B , or SCNN1G genes encoding the epithelial sodium channel (ENaC). Nevertheless, genetically investigated cases exhibiting Liddle’s-like phenotypes in the elderly population remain exceptionally rare. Methods We report a 61-year-old male admitted with recurrent limb weakness and resistant hypertension. A comprehensive clinical workup, including biochemical profiles, RAAS evaluation, and 24-h ABPM, was conducted to exclude common secondary causes. Following informed consent, whole-exome sequencing (WES) was performed, with candidate variants validated by Sanger sequencing and assessed per ACMG/AMP guidelines. To guide therapeutic management, a narrative literature review of similar cases was also performed searching PubMed, Web of Science, and CNKI using keywords like "Liddle syndrome," "elderly," "hypertension," and "hypokalemia.". Results Admission tests showed hypokalemia (2.94 mmol/L), compensated metabolic alkalosis, and suppressed renin-aldosterone levels. 24-h ABPM indicated severe blood pressure fluctuations up to 185/120 mmHg. Genetic testing revealed three heterozygous variants of uncertain significance (VUS)— CYP3A5 (c.1253 + 83C > T), SCNN1G (c.1727A > G, p.Lys576Arg), and WNK1 (c.5636A > T, p.Asp1879Val)—without any known pathogenic variants. A diagnostic trial with triamterene (50 mg twice daily) restored normal potassium levels (> 3.5 mmol/L). After a 30-day combination therapy of controlled-release nifedipine and irbesartan, blood pressure stabilized between 110 and 133 and 69-85 mmHg. Conclusion We report an elderly patient with chronic hypokalemia and resistant hypertension. After ruling out common secondary causes (for example, primary aldosteronism, Cushing's syndrome, pheochromocytoma), Liddle's-like syndrome was clinically diagnosed based on the low-renin/low-aldosterone biochemical phenotype, compensated metabolic alkalosis, literature review, and a selective response to triamterene. This case suggests that Liddle's-like syndrome must be considered in the differential diagnosis of hypokalemic hypertension in older adults to ensure early and targeted therapy.